The Socialisation of Groundnut-based Tempeh Making (Arachis hypogaea) in Gue Village, Kuta Baro Sub-district, Aceh Besar District - Aprita, Ika Rezvani; Sri Agustina; Chairil Anwar; Irhami; Endiyani; Maghfirah; Zulvia Maika Letis; Humeira; Suraiya Nazlia; Suri Purnama Febri (Fakultas Pertanian, Universitas Samudra, 2024)
Gue Village, located in Kuta Baro Sub-district, Aceh Besar District, has a large population, and most of the population works as farmers. This is the basis for choosing the location of community service activities. The Community Service Team (PkM) consisting of several lecturers assisted by several students conducted a survey and situation analysis in the village so that problems in the village could be identified. The survey results showed the problems faced by the community, namely the low level of community knowledge about diversification of processed food products, especially in peanut commodities. This is the basis for the implementation of community service activities to make tempeh made from peanut raw materials. This activity aims to socialise the community to be able to increase knowledge and skills through the use of peanuts as raw material for making tempeh in Gue village. The result of this community service activity is that the community is able to make tempeh products from peanut raw materials.